Economic impact of preventing brain metastases with alectinib in ALK-positive non-small cell lung cancer. (May 2018) - Burudpakdee, C.; Wong, W.; Seetasith, A.; Corvino, F.A.; Yeh, W.; Gubens, M.
Highlights: Healthcare costs and resource use were assessed in ALK+ NSCLC patients during variable, up to 24 months, of follow up. Brain metastasis poses a significant economic burden in ALK+ NSCLC patients. Alectinib may potentially reduce healthcare costs by preventing or delaying brain metastasis. Abstract: Objectives: Despite improved progression-free survival, most patients treated with the first generation ALK inhibitor crizotinib ultimately experience central nervous system (CNS) progression. Brain metastases (BM) are associated with high clinical burden in patients with advanced anaplastic lymphoma kinase positive (ALK+) non-small cell lung cancer (NSCLC). In this study we estimate the real-world economic burden of BM in newly diagnosed ALK+ NSCLC patients and investigate whether alectinib, a second generation ALK inhibitor that delays CNS progression, may help reduce healthcare costs in patients with ALK+ NSCLC. Materials and methods: Cost of BM was measured in ALK+ NSCLC patients identified from a stacked PharMetrics Plus and MarketScan claims database from January 2008 to March 2016 and December 2015, respectively. Per patient per month (PPPM) cost of BM was calculated as the difference in baseline-adjusted total costs in patients with and without BM over a variable follow-up period of up to 24 months. Cumulative incidence of new BM was derived from 88 alectinib-treated and 93 crizotinib-treated patients without baseline BM in a randomized phase III clinical trial, ALEX (NCT02075840). Costs of BM per patient were then calculated by applying the PPPM BM cost to the number of incident BM patients in each treatment cohort. Results: 207 patients with no BM and 198 with BM were selected from the claims database. Total cost of BM was estimated at 6, 029 PPPM. 24-month cumulative incidence rates of BM from the clinical trial were 7.2% and 45.3% for alectinib and crizotinib, respectively. Over follow-up, alectinib was estimated to reduce BM-related costs by 41, 434 per patient compared to crizotinib. Conclusion: BM is associated with substantial economic burden. Alectinib was estimated to reduce BM-related costs by preventing or delaying the occurrence of BM compared to crizotinib.